A randomized clinical trial of the effects of brief versus extended opioid overdose education on naloxone utilization outcomes by individuals with opioid use disorder. (1st August 2022) - Jones, Jermaine D.; Campbell, Aimee N.; Brandt, Laura; Metz, Verena E.; Martinez, Suky; Wall, Melanie; Corbeil, Thomas; Andrews, Howard; Castillo, Felipe; Neale, Joanne; Strang, John; Ross, Stephen; et al.
Abstract: Background: Overdose education and naloxone distribution (OEND) trains people who use opioids (PWUO) in how to intervene in cases of opioid overdose but best practices have not been assessed empirically. Methods: PWUO along with a significant other (SO) were randomized to one of three training conditions. In the Treatment-as-Usual (TAU) condition, participants were randomized to receive minimal overdose-related education. In the extended training (ET) condition, PWUO received an extended training, while their SO received no overdose training. In the final condition, both the participant and SO received the extended overdose training (ETwSO). Outcome measures were naloxone use and overdose knowledge and competency assessed immediately before and after training, and at 1-, 3-, 6-, and 12-month timepoints following training. Results: Three hundred and twenty-one PWUO (w/ a SO) were randomized. All intensities of OD training were associated with sustained increases in OD knowledge/ competency (versus pre-training baseline p's < 0.01). PWUO intervened in 166 ODs. The 12-month incidence of naloxone use did not significantly differ between groups. Extended training (ET + ETwSO) compared to TAU resulted in significantly greater naloxone utilization by: 30 days (10.1% vs 4.1%, p = 0.041), 60 days (16.4% vs 5.2%, p<0.001) and 90 days (17.9% vs 9.5%, p = 0.039). Conclusions: All intensities of OD training were associated with sustained increases in OD knowledge and competency, and equivalent rates of successful naloxone use. More extensive training increased naloxone utilization during the first 3 months. However, the benefits of more comprehensive training should be balanced against feasibility.